Building Environmental Awareness With A Waste Incineration And Maintenance Program In Tegal Sari Village, Walantaka District, Serang City - Khaeruman Khaeruman; Mohamad Bayi Tabrani; Riani Puasarin; Fitriyansyah Fitriyansyah; Arya Galuh Sidadipraja (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This community service program aimed to enhance environmental awareness through the development and maintenance of a controlled waste incineration facility in Tegal Sari Village, Walantaka District, Serang City. The program was implemented using a participatory and educational approach that actively involved community members in the planning, construction, utilization, and maintenance processes. Activities included environmental education, group discussions, hands-on training, and collective action, enabling residents to understand the negative impacts of improper waste burning on health and the environment. The results indicated a significant shift in community attitudes and behaviors toward more responsible waste management practices. Residents became more aware of environmental risks and demonstrated increased participation in maintaining cleanliness and sustainability. Furthermore, the program strengthened social cohesion, encouraging collective responsibility and long-term engagement in environmental protection. The integration of technical solutions and social empowerment proved effective in fostering sustainable behavioral change. This program contributed not only to environmental improvement but also to community capacity building. The model has strong potential for replication in other rural areas facing similar waste management challenges, emphasizing the importance of community-based environmental interventions.